Temperature-controlled Laminar Airflow (TLA) in symptomatic severe asthma – a post hoc analysis of severe exacerbations, quality of life and health economics - A. J. Chauhan; G. Eriksson; W. Storrar; T. Brown; S. Peterson; F. Radner; L. G. D’Cruz; P. Miller; L. Bjermer (BMC Pulmonary Medicine, 2022)
Abstract Purpose Uncontrolled severe asthma constitutes a major economic burden to society. Add-ons to standard inhaled treatments include inexpensive oral corticosteroids and expensive biologics. Nocturnal treatment with Temperature-controlled Laminar Airflow (TLA; Airsonett®) could be an effective, safe and cheaper alternative. The potential of TLA in reducing severe asthma exacerbations was addressed in a recent randomised placebo-controlled trial (RCT) in patients with severe asthma (Global Initiative for Asthma (GINA) step 4/5), but the results were inconclusive. We re-analysed the RCT with severe exacerbations stratified by the level of baseline asthma symptoms and Quality of Life. Methods More uncontrolled patients, defined by Asthma Control Questionnaire 7 (ACQ7) > 3, EuroQoL 5-Dimension Questionnaire Visual Analogue Scale (EQ5D-VAS) ≤ 65 and Asthma Quality of Life Questionnaire (AQLQ) ≤ 4 were selected for re-analysis. The rates of severe asthma exacerbations, changes in QoL and health-economics were analysed and compared between TLA and placebo. Results The study population included 226 patients (113 TLA / 113 placebo.) The rates of severe asthma exacerbations were reduced by 33, 31 and 25% (p = 0.083, 0.073, 0.180) for TLA compared to placebo, dependent on selected control measures (ACQ7, EQ5D-VAS, AQLQ, respectively). For patients with less control defined by AQLQ≤4, the difference in mean AQLQ0-12M between TLA and placebo was 0.31, 0.33, 0.26 (p = 0.085, 0.034, 0.150), dependent on selected covariate (AQLQ, EQ5D-VAS, ACQ7, respectively). For patients with poor control defined by ACQ7 > 3, the difference in EQ5D-5 L utility scores between TLA and placebo was significant at 9 and 12 months with a cost-effective ICER. The results from the original study did not demonstrate these differences. Conclusion This post hoc analysis demonstrated an effect of TLA over placebo on severe exacerbations, asthma control and health economics in a subgroup of patients with more symptomatic severe allergic asthma. The results are consistent with the present recommendations for TLA. However, these differences were not demonstrated in the full study. Several explanations for the different outcomes have been outlined, which should be addressed in future studies. Funding NIHR Health Technology Assessment Programme and Portsmouth Hospitals NHS Trust.